2005
DOI: 10.1111/j.1442-200x.2005.02020.x
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical hypothyroidism caused by a mutation of the thyrotropin receptor gene

Abstract: Key wordssubclinical hypothyroidism, thyrotropin receptor mutation.Subclinical hypothyroidism is defined as an elevated serum TSH concentration, and normal serum free thyroxine (T 4 ) and 3,5,3 ′ -triiodothyronine (T 3 ) concentrations associated with few or no symptoms or signs of hypothyroidism. 1,2 Recently, not only infants with overt hypothyroidism but also those with subclinical or mild hypothyroidism have been found by neonatal screening for congenital hypothyroidism.We identified a missense mutation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 15 publications
(32 reference statements)
0
18
1
Order By: Relevance
“…123 I scintigraphy showed a normal-sized eutopic thyroid gland. Her basal serum TSH level (18.8 mU/l) remained elevated, but the report did not mention serum T4 or FT4 level at that time [19]. So the thyroid function in older children with a homozygous R450H mutation of TSHR remains unclear.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…123 I scintigraphy showed a normal-sized eutopic thyroid gland. Her basal serum TSH level (18.8 mU/l) remained elevated, but the report did not mention serum T4 or FT4 level at that time [19]. So the thyroid function in older children with a homozygous R450H mutation of TSHR remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In the Japanese population, five different loss of function mutations (R450H, G498G, V473I, R519C, R519G) have been found [12, 17, 19, 20]. The R450H mutation affects the first cytoplasmic loop of the TSHR, and all patients with TSH resistance resulting from TSH receptor mutations identified in Japan possessed R450H mutation at least in one allele [12, 17, 19, 20].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alternatively, it may occur following a subacute, postpartum, painless thyroiditis, or after a partial thyroidectomy (19; 37) Shibayama and colleagues used neonatal screening to identify a mutation in the thyrotropin receptor (TSHR) gene in a patient with subclinical hypothyroidism. In their study, they found a mild dysfunction of the R450H mutant on the TSHR gene, and it correlated it with mild clinical and biochemical manifestations (121).…”
Section: Etiologymentioning
confidence: 99%